The roles of serum vitamin D and tobacco smoke exposure in insomnia: a cross-sectional study of adults in the United States - Gao, Tianci; Hou, Mengxing; Wang, Qianfei; Liu, Dong; Chen, Fenqiao; Xing, Yueyi; Mei, Jianqiang (Frontiers in Nutrition, 2023)
Aim: Tobacco smoke exposure and vitamin D (VD) status were both associated with insomnia. However, the combined effect between smoking and VD had not been discussed on insomnia. Herein, this study aims to explore the role of VD in the association between tobacco smoke exposure and insomnia.: Data of adults were extracted from the National Health and Nutrition Examination Surveys (NHANES) database in 2005-2008 in this cross-sectional study.Weighted univariate and multivariate logistic regression analyses were used to explore the associations between serum cotinine, serum VD, and insomnia respectively. A surface diagram was drew to reflect the effect of VD on association between serum cotinine and insomnia. In addition, the potential regulating effect of VD in subgroups of smoking status was also performed. The evaluation index was odds ratios (ORs) with 95% confidence intervals (CIs).Results: Among the eligible participants, 1,766 had insomnia. After adjusting for covariates, we found that elevated serum cotinine levels were associated with higher odds of insomnia [OR=1.55, 95%CI: (1.22, 1.97)]. However, the relationship between serum VD level and insomnia was not significant (P=0.553). Higher serum cotinine level was also associated with higher odds of insomnia [OR=1.52, 95%CI: (1.17, 1.98)] when serum VD level <75 nmol/L, and however, this relationship become not significant when serum VD concentration elevated (P=0.088). Additionally, the potential regulating effect of VD was also found in adults who were not smoking.Vitamin D status and tobacco smoke exposure in insomnia 4 tobacco smoke exposure and insomnia. Further studies are needed to clarify the causal relationships between VD, tobacco smoke exposure, and insomnia respectively.